Cloning and characterization of two groESL operons of Rhodobacter sphaeroides: transcriptional regulation of the heat-induced groESL operon. - Lee, W T (1997)
The nonsulfur purple bacterium Rhodobacter sphaeroides was found to contain two groESL operons. The groESL1 heat shock operon was cloned from a genomic library, and a 2.8-kb DNA fragment was sequenced and found to contain the groES and groEL genes. The deduced amino acid sequences of GroEL1 (cpn60) and GroES1 (cpn10) were in agreement with N-terminal sequences previously obtained for the isolated proteins (K. C. Terlesky and F. R. Tabita, Biochemistry 30:8181-8186, 1991). These sequences show a high degree of similarity to groESL genes isolated from other bacteria. Northern analysis indicated that the groESL1 genes were expressed as part of a 2.2-kb polycistronic transcript that is induced 13-fold after heat shock. Transcript size was not affected by heat shock; however, the amount of transcript was induced to its greatest extent 15 to 30 min after a 40 degrees C heat shock, from an initial temperature of 28 degrees C, and remained elevated up to 120 min. The R. sphaeroides groESL1 operon contains a putative hairpin loop at the start of the transcript that is present in other bacterial heat shock genes. Primer extension of the message showed that the transcription start site is at the start of this conserved hairpin loop. In this region were also found putative -35 and -10 sequences that are conserved upstream from other bacterial heat shock genes. Transcription of the groESL1 genes was unexpectedly low under photoautotrophic growth conditions. Thus far, it has not been possible to construct a groESL1 deletion strain, perhaps indicating that these genes are essential for growth. A second operon (groESL2) was also cloned from R. sphaeroides, using a groEL1 gene fragment as a probe; however, no transcript was observed for this operon under several different growth conditions. A groESL2 deletion strain was constructed, but there was no detectable change in the phenotype of this strain compared to the parental strain.